2020
DOI: 10.1088/1361-6668/ab9f64
|View full text |Cite
|
Sign up to set email alerts
|

Large enhancement of the in-field critical current density of YBCO coated conductors due to composite pinning landscape

Abstract: YBa2Cu3O7-based coated conductors (CCs) achieve the highest critical current densities (J c) of any known superconductor and are a key technology for applications such as rotatory machines, high-field magnets and power transmission. Incorporation of nano-sized non-superconducting second phases as additional vortex pinning centers has been considered the most amenable route to further enhance J c at an industrial scale, and has been successfully used in commercial CCs. The re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 76 publications
0
10
0
Order By: Relevance
“…These experiments show, except in low magnetic fields, that there is an initial improvement in J c with increasing irradiation dose, followed by a decrease in both J c and T c and eventual complete loss of superconductivity. Both the fluence at which the peak J c improvement is reached and the amount of any improvement are considered to be dependent on the sample temperature, type of projectile and the direction of the applied field [9][10][11][12]. For both ion and neutron irradiation, the degree of anisotropy in the superconducting properties of the textured REBCO in CC was also found to decrease with irradiation dose [10,[12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These experiments show, except in low magnetic fields, that there is an initial improvement in J c with increasing irradiation dose, followed by a decrease in both J c and T c and eventual complete loss of superconductivity. Both the fluence at which the peak J c improvement is reached and the amount of any improvement are considered to be dependent on the sample temperature, type of projectile and the direction of the applied field [9][10][11][12]. For both ion and neutron irradiation, the degree of anisotropy in the superconducting properties of the textured REBCO in CC was also found to decrease with irradiation dose [10,[12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…Both the fluence at which the peak J c improvement is reached and the amount of any improvement are considered to be dependent on the sample temperature, type of projectile and the direction of the applied field [9][10][11][12]. For both ion and neutron irradiation, the degree of anisotropy in the superconducting properties of the textured REBCO in CC was also found to decrease with irradiation dose [10,[12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…large J c enhancement due to random 0D irradiation defects 12,13) and "dimpled" J c -versus-magnetic-field-angle curves 14,15) , suggesting a useful platform for reexamining the intrinsic properties of pins in YBCO films. In those studies using FF-MOD, J c sf was not enhanced, similarly to other deposition methods, 1,10,11) but irradiation defects had been introduced only for random 0D defects (ion energy E i < 5 MeV) but not for discontinuous/continuous 1D defects (E i > 20 MeV). In our present study, we observed significant enhancement (up to 63%) in J c sf in FF-MOD YBCO films at 77 K when discontinuous 1D irradiation defects were 5-10 nm in diameter, ∼20 nm in size along an ion track, had a ∼20 nm gap between defects in an ion track, and were directed in the caxis.…”
Section: Introductionmentioning
confidence: 95%
“…Indeed, it has been repeatedly reported that, in YBCO films, introduction of vortex-pinning centers (pins) by ion irradiation in the form of amorphous domains [3][4][5][6][7][8][9] causes an increase in J c only in applied magnetic fields but not in self-field. 1,10,11) Lack of a sufficient number of examples of "J c sf " enhancement in YBCO films makes it unclear what type of microstructure in the material is ideal for application (i) above, namely, for J c sf at high temperatures. 1,2) In this work, we performed 24-84 MeV Au-ion irradiation on 1 μm thick YBCO films prepared by fluorine-free metal organic deposition (FF-MOD) to gain insight into what type of microstructure in YBCO films is effective for J c sf at high temperatures.…”
Section: Introductionmentioning
confidence: 99%
“…The presence of random point defects 37,38 also improved the ineld J c , especially at temperatures below 40 K. Secondary phase nanorods/nanocolumns 29,39,40 or irradiated columnar defects 26,31 enhanced J c mainly when H is parallel to the c-axis (H||c), especially at high magnetic elds and high temperatures; the same occured for natural defects such as twin boundaries 41,42 and dislocations 43,44 . Lately, hybrid nanostructures combining various defects [45][46][47][48][49][50] have also been investigated, with the aim of merging gains. However, only a few studies cover large magnetic eld and temperature ranges 6,51−53 .…”
Section: Introductionmentioning
confidence: 99%